THE EFFECTIVENESS OF USING PODCASTS ON SPOTIFY TO IMPROVE ENGLISH LISTENING SKILLS OF THE TENTH GRADE STUDENTS AT SMAN 1 SUKOMORO - Dini Astiyanisa; Henny Roesellaningtias r (Journal of English Language Education, 2025)
English listening skills are essential in the process of learning English. However, many students face challenges in developing these skills due to insufficient practice, external distractions, and internal barriers such as lack of motivation and concentration. Observations have shown that students in class X-2 at SMAN 1 Sukomoro still have suboptimal listening comprehension, affecting the teaching and learning process. This study aims to determine the effectiveness of using podcast on Spotify to improve the English listening skills of students in class X-2 at SMAN 1 Sukomoro for the academic year 2023/2024. This research employs a quantitative method with a pretest and posttest design (one-group) to measure the English listening skills before and after using podcast on Spotify. The sample consists of students in class X-2 at SMAN 1 Sukomoro. The convenience sampling was used in this research. Data were collected through the English listening skills tests and analyzed using statistical descriptive and statistical t-tests to determine the effectiveness of the intervention. The findings indicate a significant difference of the students' English listening skills after using podcast on Spotify. The average pretest score was 66,36, while the average posttest score increased to 80,60. The t-test results showed a tcount of 17,8 with a ttable< 0.05 is 1,692, indicating a significant difference between pretest and posttest scores. The average score improvement was 14,24, which is 21,45% improvements to demonstrating the effectiveness of podcasts as a learning aid. Using podcast on Spotify effectively enhances students' English listening skills. These results suggest that integrating digital audio technology in language learning can provide significant benefits. Further research is needed to explore long-term impacts and applications in other learning contexts.